Utilization of dried bakery product by finishing beef steers - C.T. Milton; Robert T. Brandt Jr. (Kansas Agricultural Experiment Station Research Reports, 1993)
One hundred forty-four medium-framed crossbred steers averaging 857 lb were used to evaluate steer performance and determine net energy (NE) values of finishing diets that included dried bakery product (DBP). DBP replaced corn in the control diet at 15 or 30% of dietary DM. DM intake was depressed 6.5% by inclusion of 30% DBP. No differences in daily gain (P>.3) or feed efficiency (P>.9) were observed by replacing corn with DBP. Dietary values of NEm and NEg, calculated from animal performance, were not affected (P>.7) by the inclusion of DBP. Kidney, pelvic, and heart fat (KPH) (P<.05) and 12th rib fat thickness (P<.1) were increased linearly with inclusion of DBP, whereas other carcass characteristics were unaffected. These data indicate the DBP (10% rice hulls included) has an energy value similar to that of corn grain, although the optimal inclusion level of DBP appears to be below 30% of dietary DM.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Finishing steers; Dried bakery product; Net energy